Functional evaluation of constructed pseudo-endogenous microRNA-targeted myocardial ultrasound nanobubble - Ainiwan, Ailifeire; Wei, Yuanyuan; Dou, Jing; Tang, Lingpeng; Mu, Yuming; Guan, Lina (Frontiers in Medicine, 2023)
Background Stem cell transplantation is one of the treatment methods for acute myocardial infarction (AMI). MicroRNA-1 contributes to the study of the essential mechanisms of stem cell transplantation for treating AMI by targeted regulating the myocardial microenvironment after stem cell transplantation at the post-transcriptional level. Thus, microRNA-1 participates in regulating the myocardial microenvironment after stem cell transplantation, a promising strategy for the Stem cell transplantation treatment of AMI. However, the naked microRNA-1 synthesized is extremely unstable and non-targeting, which can be rapidly degraded by circulating RNase. Herein, to safely and effectively targeted transport the naked microRNA-1 synthesized into myocardial tissue, we will construct pseudo-endogenous microRNA-targeted myocardial ultrasound nanobubble pAd-AAV-9/miRNA-1 NB and evaluate its characteristics, targeting, and function. Methods The pAd-AAV-9/miRNA-1 gene complex was linked to nanobubble NBs by the “avidin-biotin bridging” method to prepare cardiomyocyte-targeted nanobubble pAd-AAV-9/miRNA-1 NB. The shape, particle size, dispersion, and stability of nanobubbles and the connection of pAd-AAV-9/miRNA-1 gene complex to nanobubble NB were observed. The virus loading efficiency was determined, and the myocardium-targeting imaging ability was evaluated using contrast-enhanced ultrasound imaging in vivo. The miRNA-1 expression level in myocardial tissue and other vital organs ex vivo of SD rats was considered by Q-PCR. Also, the cytotoxic effects were assessed. Results The particle size of NBs was 504.02 ± 36.94 nm, and that of pAd-AAV-9/miRNA-1 NB was 568.00 ± 37.39 nm. The particle size and concentration of pAd-AAV-9/miRNA-1 NBs did not change significantly within 1 h at room temperature (p > 0.05). pAd-AAV-9/miRNA-1 NB had the highest viral load rate of 86.3 ± 2.2% (p < 0.05), and the optimum viral load was 5 μL (p < 0.05). pAd-AAV-9/miRNA-1 NB had good contrast-enhanced ultrasound imaging in vivo. Quantitative analysis of miRNA-1 expression levels in vital organs ex vivo of SD rats by Q-PCR showed that pAd-AAV-9/miRNA-1 NB targeted the myocardial tissue. Q-PCR indicated that the expression level of miRNA-1 in the myocardium of the pAd-AAV-9/miRNA-1 NB + UTMD group was significantly higher than that of the pAd-AAV-9/miRNA-1 NB group (p < 0.05). pAd-AAV-9/miRNA-1 NB had no cytotoxic effect on cardiomyocytes (p > 0.05). Conclusion The pAd-AAV-9/miRNA-1 NB constructed in this study could carry naked miRNA-1 synthesized in vitro for targeted transport into myocardial tissue successfully and had sound contrast-enhanced imaging effects in vivo.